Competing tactics: How the interplay of tactical approaches shapes movement outcomes on the market for ethical fashion - Philip Balsiger (Max Planck Institute for the Study of Societies, 2012)
Social movements use a variety of tactical approaches to change markets. Through a case study of ethical fashion in Switzerland, this paper looks at how the interplay between different tactical approaches pursued by movement actors shapes the growth of the ethical clothing market. Most studies on the influence of social movements look at single tactical approaches, and rarely discuss tactical competition and its role on outcomes. This paper adopts an interactionist field perspective to see this interplay at work. Three tactical approaches are identified: campaigning, collaboration initiatives, and the promotion of alternative niches. This paper points out the different cultural and social backgrounds behind these approaches and discusses their relationships with one another. It highlights how different tactical approaches may draw on one another, but also stresses instances of tactical competition. In particular, the analysis reveals how collaboration initiatives could be used by firms to sidestep more encompassing demands from the campaign. Furthermore, the analysis highlights how the specific definition of the niche, emerging as an outcome of a dynamic involving campaign actors, collaboration initiatives and firms, constitutes an obstacle to the creation of an alternative niche as advocated by its promoters. – – Soziale Bewegungen nutzen verschiedene Taktiken für ihre Einflussnahme auf Märkte. Am Fallbeispiel des Schweizer Ethik-Modemarkts analysiert dieses Papier, wie das Wechselspiel verschiedener Taktiken das Wachstum dieses Marktes beeinflusst. Die Mehrzahl der Untersuchungen über den Einfluss sozialer Bewegungen konzentriert sich auf eine bestimmte Taktik und lässt taktischen Wettbewerb und dessen Auswirkung auf die Ergebnisse außen vor. Im Gegensatz dazu nimmt dieses Papier eine interaktionistische Perspektive ein und analysiert die Wechselwirkungen verschiedener Taktiken im Marktgeschehen. Dabei werden drei Varianten der taktischen Einflussnahme identifiziert: Kampagnen, Kollaborationsinitiativen sowie die Bewerbung alternativer Nischenmärkte. Das Papier zeigt die verschiedenen kulturellen und gesellschaftlichen Hintergründe dieser Herangehensweisen auf und diskutiert die Wechselbeziehungen. Es macht weiterhin deutlich, wie verschiedene taktische Herangehensweisen aufeinander aufbauen und auch, wie sie miteinander konkurrieren. Insbesondere deckt die Analyse auf, wie Kollaborationsinitiativen von Unternehmen genutzt werden könnten, um aus einer Kampagne resultierende weitergehende Anforderungen umgehen zu können. Darüber hinaus wird deutlich, wie die explizite Definition der Marktnische, die als Folge einer Dynamik entstanden ist, die Kampagnenakteure, Kollaborationsinitiativen und Firmen involviert, die Schaffung eines von ihren Befürwortern propagierten alternativen Nischenmarkts behindert.
Keywords: 300; Soziale Bewegung; Mode; Ethik; Schweiz